(untitled) (LACCEI, 2024)
On-time deliveries are considered a strategic factor for the market positioning of companies. Such is the case of the company under study where only 76.5% of orders arrive on time, compared to 90.2% of companies in the same sector in Colombia. The causes of the problem are an inadequate management of the raw material warehouse processes, causes such as the lack of organization of the physical space that lengthen the preparation of orders, inefficient inventory control processes at the entrance and inside the warehouse and inadequate handling. These have caused losses of raw materials due to pyrolysis, shortages, and delays in production and therefore the rescheduling of the delivery date of orders. In order to improve these processes, we implemented the 5S and a redesign of the warehouse, simple sampling, ABC analysis, cyclic counting and EOQ model. As a result, an increase in orders delivered on time of 12.53% and an economic impact of S/. 1,468,580 in a period of 5 years excluding implementation costs and a net cash flow in the first year of S/. 36,052.